Exposure to indoor and outdoor air pollution among children under five years old in urban area - A.K.R. Kouao; E.T. N’datchoh; V. Yoboue; S. Silue; H. Attoh; M. Coulibaly; T. Robins (Global Journal of Environmental Science and Management)
Indoor air pollution associated with cooking and heating biomass fuel burning is estimated to be responsible for 7 million deaths in 2016 and most of these deaths occur in low and middle income countries. In Côte d'Ivoire, 73% of the population is reported using biomass (charcoal or wood) for cooking. The active device 3M EVM-7 was used to measure PM2.5 daily average concentrations inside and outside households in areas close (Andokoi) and far (Lubafrique) to an industrial zone in two popular neighborhoods of Yopougon, the largest and most populated municipality of the city of Abidjan (Côte d’Ivoire). PM2.5 daily average concentrations indoors and outdoors are respectively 121±12 µg/m3 and 117±8 µg/m3 in Andokoi and 32±3 µg/m3 and 41±4 µg/m3 in Lubafrique well above the World Health Organization guideline value (25 µg/m3) for air quality. Using multivariable models, the results were the number of windows in bedrooms and kitchens located outdoor were negatively correlated with the concentration of indoor PM2.5. The outdoor concentrations of PM2.5, were higher according to the cooking fuel type.